The effect of shooting distance on movement variability in basketball - Robins, M.; Wheat, J.; Irwin, G.; Bartlett, R. (Journal of Human Movement Studies, 2006)
The purpose of the study was to examine the effect of shooting distance on continuous and discrete measures of movement variability in basketball. Six skilled, male basketball players performed five standardised successful shots at distances of 4.25, 5.25 and 6.25m. The findings provided evidence of compensatory variability by means of a sequential increase in movement variability along the kinematic chain at ball release. Compensatory variability was proposed to minimise the variability of projectile release parameters. As distance increased, significant decreases were found for several of the discrete and continuous measures of movement variability. Specifically, a reduction in continuous coordination variability was observed for the Standard deviation of continuous relative phase for the wrist-elbow (p=0.01) and wrist-shoulder (p=0.01) joint couplings. A decrease was also found in the variability of continuous relative phase for the wrist-elbow (p=0.0001), elbow-shoulder (p=0.07) and wrist-shoulder (p=0.001) joint couplings at ball release. Both of these findings were attributed to the larger margin for error at closer distances that permitted greater exploration of the available phase-space.